Human Impact on Wildlife and Ecosystems for Sustainable Development - Chaudhry, Priyanka (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
The intricate relationship between human activities and the natural environment has resulted in profound implications for wildlife and ecosystems worldwide. Human-induced factors such as deforestation, habitat destruction, pollution, climate change, and overexploitation of species have significantly altered ecosystems, leading to biodiversity loss and ecosystem degradation. The concept of sustainable development emerges as a crucial framework, emphasizing the integration of conservation efforts into development agendas. It necessitates a delicate balance wherein socio-economic progress aligns with ecological sustainability. This chapter explores the multifaceted impacts of human actions such as deforestation, habitat destruction, pollution, climate change, overexploitation and species decline as key challenges having an adverse effect on wildlife and ecosystems and highlights possible sustainable development strategies to foster a harmonious balance between human needs and environmental conservation for the betterment of wildlife and ecosystem restoration.